اختيار المواد متغيّرة الطور (PCM) من أجل تكييف هواء المنازل في فصل الصيف - أحمد مها (Latakia University Journal -Engineering Sciences Series, 2017)
المواد متغيرة الطور (PCM) عبارة عن مواد تمتص كمية كبيرة من الطاقة الحرارية عند تغير الطور صلب/سائل وتقوم بتحريرها عند التصلب. لذلك إحدى استخدامات المواد متغيرة الطور هي تخزين الطاقة الحرارية، حيث يمكن للمواد متغيرة الطور المدمجة مع مواد البناء أن تزيد من العطالة الحرارية للأبنية وأن تخفض الطاقة اللازمة للتدفئة والتكييف. يعتبر هذا مناسباً بشكل خاص للأبنية التجارية التي تكون عادة ذات هيكل خفيف. لكن الإيصالية الحرارية الضعيفة للمواد متغيرة الطور تُعتبر من أهم الخواص التي تحدّ من استخدامها. الهدف من هذه الدراسة هو اقتراح اختيار مواد ذات إيصالية كافية لأن تسمح بتحقيق التكييف خلال فصل الصيف لتحدّ بل لتلغي استخدام الطاقة (الكهربائية أو الوقود) باستخدام جدران حاوية على مواد متغيرة الطور. تتكون الدراسة من جزأين: ـ الجزء الأول يستعرض مشاكل الدراسة، ويبيّن المجال الذي يمكن ضمنه استخدام المواد متغيرة الطور كنظام تكييف سلبي. ـ الجزء الثاني وضع معايير الاختيار التي ستسمح مبدئيّاً باختيار مواد معينة. The Phase Change Materials (PCM) are materials which absorb a great quantity of energy during the change of phase solid /liquid and relies it during solidification An application of these materials is thermal energy storage. The PCM integrated into materials of the building can reinforce their inertia and reduce the power necessary for the heating and air conditioning. This is particularly true for the buildings of the tertiary sector whose envelope is light. Nevertheless, one of the characteristics which limits the use of the PCM is their low conductivity. The objective of this article is to propose a selection of materials having a conductivity high enough to make it possible to ensure an air conditioning in summer while limiting, even while removing, the use of energy (electricity or fuel) thanks to walls containing these PCMs. This article consists of two parts: - The first part exposes the problems of the study and specifies the context in which the use of a PCM as a passive air conditioning system fits. - The second part fixes the selection criteria which will allow, in a first approach to choose certain materials